2013
DOI: 10.1093/europace/eut250
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic brain lesions following laserballoon-based pulmonary vein isolation

Abstract: Following laserballoon-based PVI, new asymptomatic brain lesions were detected in 11.4% of patients. A higher CHA2DS2VASc score, but not the ablation technology utilized, was the only associated risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 13 publications
2
58
2
Order By: Relevance
“…The endoscopic ablation system (EAS, CardioFocus, Inc., Marlborough, MA, USA) incorporates a compliant balloon and a laser source that allow deployment of point‐by‐point lesions under direct visual guidance . Data on the feasibility, safety, and clinical outcome of EAS‐based PVI have recently been published . The current prospective study sought to compare wide circumferential to separate isolation of individual PVs using the EAS and assess acute procedural success, safety, and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The endoscopic ablation system (EAS, CardioFocus, Inc., Marlborough, MA, USA) incorporates a compliant balloon and a laser source that allow deployment of point‐by‐point lesions under direct visual guidance . Data on the feasibility, safety, and clinical outcome of EAS‐based PVI have recently been published . The current prospective study sought to compare wide circumferential to separate isolation of individual PVs using the EAS and assess acute procedural success, safety, and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…While some groups have defined the ''new MRI-detected lesion'' as a hyperintense diffusion-weighted imaging (DWI) lesion with reduced apparent diffusion coefficient (ADC) and T2-weighted fluid-attenuated inverse recovery sequence (FLAIR) positivity, 10,13-17 a few others have used a more sensitive definition without the FLAIR positivity. 11,[18][19][20][21][22][23][24][25][26] There is much controversy regarding the significance of SCLs/SCEs and their long-term consequences. In addition to the structural MRI findings, several recent studies have suggested a strong association with function, correlating SCLs/SCEs and cognitive decline, as well as dementia.…”
Section: Silent Cerebral Lesions or Eventsmentioning
confidence: 99%
“…7,20,34,35 A small proportion of the lesions seem to be larger than 10 mm and seen predominantly in the cerebellum. [8][9][10][11]13,14,18,21,[36][37][38] Although most studies reporting post-AF ablation SCLs/SCEs were performed using 1.5-Tesla MRIs, one study using a 3-Tesla high-resolution MRI reported a two to three times increase in the incidence of the lesions in patients undergoing left atrial catheter ablation independent of the respective balloon-based catheter devices. The new lesions seen in this study were not associated with cognitive decline in patients after the ablation, suggesting a mere increase in the imaging sensitivity rendered by the higher spatial resolution rather than increased cerebral embolization during the procedure.…”
Section: Silent Cerebral Lesions or Eventsmentioning
confidence: 99%
See 2 more Smart Citations